Yu Feian, Chinese Painting Colors. Studies of their Preparation in Traditional and Modern Times, University of Washington Press y Hong Kong University Press, Seattle y Hong Kong (traducción de Jerome Silbergeld y Amy McNair), 1988, xiv + 93 pp. - B., R. C. (Estudios de Asia y África, 1990)
-